Оцінка впливу фінансово-економічної кризи та пандемії COVID-19 на національний ринок праці - Шамілева, Л.Л.; Хандій, О.О. (Економічний вісник Донбасу, 2020)
У статті досліджено вплив карантинних обмежень під час світової пандемії COVID-19 та фінансово-економічної кризи на національний ринок праці. На основі оцінок очікуваних обсягів виробництва у 2020 році та за умови збереження досягнутого рівня продуктивності праці у попередні роки визначено можливі зміни кількості зайнятих у різних галузях економіки України. Надана характеристика негативним тенденціям скорочення попиту на персонал за галузями промисловості, у будівництві, в сфері послуг. Розраховано очікуваний обсяг вивільнення робочої сили та зростання кількості безробітних протягом кризового періоду 2020-2021 років. Запропоновано часові три етапи виходу з економічної рецесії та подолання економічних наслідків карантину, які обумовлюють зміст, характер і глибину прояву соціальних ризиків у системі соціально-трудових відносин та в сфері зайнятості. Визначено послідовність прояву соціальних ризиків, пов’я¬заних зі зниженням ділової активності підприємств, карантинними обмеженнями та інтенсифікацією цифровізації економіки та суспільства. В статье исследовано влияние карантинных ограничений во время пандемии COVID-19 и финансово-экономического кризиса на национальный рынок труда. На основе оценок ожидаемых объемов выпуска продукции и оказания услуг в 2020 году при условии сохранения достигнутого уровня производительности труда в предыдущие годы определены возможные изменения численности занятого населения в различных отраслях экономики Украины. Дана характеристика негативным тенденциям сокращения спроса на персонал в отраслях промышленности, в строительстве, в сфере услуг. Определен прогнозный объем высвобождения рабочей силы и увеличения количества безработных в течение кризисного периода 2020-2021 годов. Предложены временные этапы выхода из экономической рецессии и преодоления экономических последствий карантина, которые обусловливают содержание, характер и глубину проявления социальных рисков в системе социально-трудовых отношений и в сфере занятости. Определена последовательность проявления социальных рисков, связанных со снижением деловой активности предприятий, карантинными ограничениями и интенсификацией цифровизации экономики и общества. The impact of quarantine restrictions during the global COVID-19 pandemic and the financial and economic crisis on the national labor market was explored in the article. Possible changes in the number of people employed in various sectors of the Ukrainian economy were determined on the basis of estimates of expected production volumes and subject to maintaining the achieved level of labor productivity in previous years. The characteristic was given to the negative trends of declining demand for personnel by industry, construction, services. Metallurgical production, mechanical engineering, electricity production, textile clothing production, production of consumer durables were attributed to the main types of industrial activity, where there are very negative trends in production. The expected amount of layoffs and growth in the number of unemployed was calculated for the crisis period of 2020-2021. The reduction of staff occurred in more than a third of enterprises in construction and services, which is taken into account in the calculations. Three temporal stages of overcoming the economic recession and overcoming the economic consequences of quarantine, which determine the content, nature and depth of social risks in the system of social and labor relations and in the field of employment, were proposed. The sequence of social risks associated with declining business activity, quarantine restrictions during the COVID-19 pandemic, and the intensification of the digitalization of the economy and society has been determined. The growth of social insecurity and insufficiency of livelihoods is expected at the first stage, the risks of unemployment persist, the risks of non-compliance of labor supply with educational and professional needs of the labor market, increased labor migration, increased partial and informal employment increase in the second stage; social risks due to the intensity of digitalization increase in the third stage.